2018
DOI: 10.1177/2322093718766806
|View full text |Cite
|
Sign up to set email alerts
|

Does Emotional Intelligence Predict Leadership Effectiveness? An Exploration in Non-Western Context

Abstract: The study focuses on understanding the emotional intelligence and leadership linkages in a non-Western context. The study was conducted on a sample of 230 supervisors and subordinates drawn from branches of the banking sector in the state of Jammu and Kashmir, India. The study employs three-dimensional emotional intelligence model developed by Singh and Chadha. Emotional competency and emotional sensitivity were found to be significant antecedents of leadership effectiveness in the context under reference. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 28 publications
1
12
0
3
Order By: Relevance
“…Therefore, when we look at the issue from the point of view of educational organizations, having a strong sustainable leadership structure of the organization for a sustainable success will be the key to the successful management of the diversities within the institution. In addition, studies conducted on both educational organizations and other organizations in the literature reveal that managers’ emotional intelligence levels show positive relationships with leadership behaviors ( Qian et al, 2017 ; Boyatzis, 2018 ; Lone and Lone, 2018 ). In this respect, these findings obtained from the research are also supported by the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, when we look at the issue from the point of view of educational organizations, having a strong sustainable leadership structure of the organization for a sustainable success will be the key to the successful management of the diversities within the institution. In addition, studies conducted on both educational organizations and other organizations in the literature reveal that managers’ emotional intelligence levels show positive relationships with leadership behaviors ( Qian et al, 2017 ; Boyatzis, 2018 ; Lone and Lone, 2018 ). In this respect, these findings obtained from the research are also supported by the literature.…”
Section: Resultsmentioning
confidence: 99%
“…However, most study populations represent ‘Western’ cultures, such as the UK, USA and Australia (Emmerling & Boyatzis, 2012 ). Therefore, it is essential to question whether constructs such as emotions and leadership have different meanings in the Global South (Lone & Lone, 2018 ).…”
Section: Machiavellianism Leadership and Emotions In The Global Southmentioning
confidence: 99%
“…Primarily research has focused on the benefits of emotions in leadership (Côté et al, 2010;Lone & Lone, 2018). However, the outcomes/consequences of emotions in leadership can be prosocial and non-prosocial (Austin et al, 2007(Austin et al, , 2014.…”
Section: Dark Leadership and Emotionsmentioning
confidence: 99%
“… Silva and Coelho ( 2019 ) also demonstrated that EI affects creativity, increases task performance ( Miao et al 2018 ), and makes the project even more successful ( Doan et al 2020 ). Moreover, EI influences leadership range and effectiveness ( Issah 2018 ; Lone and Lone 2018 ). Previous studies show that EI is crucial for individuals and organizational life, especially in a school organization.…”
Section: Introductionmentioning
confidence: 99%